Alternatives to prevent the failure of RC members under close-in blast loadings. (February 2016) - Codina, Ramón; Ambrosini, Daniel; de Borbón, Fernanda
Abstract: In this paper, an experimental study of the dynamic response of reinforced concrete (RC) members protected in different ways is presented. Two alternatives for the protection of RC members are designed and studied; classical steel jacketing and a new reinforced polyurethane sacrificial layer. The mitigation of shock and absorption of energy from the blast is studied with experimental methods. For comparison purposes, a RC member without protection is also tested and studied. As expected, the steel jacketing provided excellent protection reducing the maximum final deflection as well as reducing damage to the member. On the other hand, the proposed reinforced polyurethane protection performed reasonably well. The obtained results are useful for exploring new alternatives for the protection of RC columns as well as for the calibration of numerical codes. Highlights: Alternatives of protection of RC members subjected to blast loadings are experimentally studied A new protection for columns based in polyurethane bricks reinforced with steel is proposed For comparison purposes, members without reinforcing and with steel jacketing are also tested. The steel jacketing shows excellent behaviour and the proposed protection had a good response.